ND:YAG Laser Vitreolysis as The Management of Occluded Tube After Glaucoma Drainage Device Implantation (GDD): Poster Presentation - Case Report - Resident - Iskandar, Raden Fitri Fatimah; Gustianty, Elsa; Umbara, Sonie; Prahasta, Andhika; Rifada, R. Maula (Majalah Oftalmologi Indonesia, 2023)
Introduction : Glaucoma Drainage Devices (GDD) implantation surgery can be an alternative therapy for patients with uncontrolled IOP after trabeculectomy. However, tube occlusion is a common complication of GDD implantation. Management of tube occlusion can be done using laser or with surgery. This case presents the management of vitreous occlusion of tube implant using ND:YAG laser-vitreolysis. Case Illustration : A 63 year-old male patient came with chief complaint of pain in his right eye. The patient had a history of cataract surgery on the right eye and was diagnosed with glaucoma. An examination showed IOP in the right eye was increased, vitreous in COA and lens was aphakic with posterior capsule rupture. The patient had undergone trabeculectomy, but IOP remained high, so an Aurolab Aqueous Drainage Implant (AADI) GDD implantation was performed. However, six weeks after the procedure, the IOP still increased, and an examination revealed vitreous occlusion of the GDD tube (Figure 1) . The patient underwent Zeiss ND-YAG laser-vitreolysis on his right eye (Figure 2) with laser spot size of 50?m and power of 2.1 MJ. Post laser IOP was decreased. Discussion : GDD implantation is a surgical option for primary or secondary therapy, but tube occlusion can cause implantation failure. Laser-vitreolysis is a non- invasive modality to treat tube occlusion caused by vitreous. Conclusion : GDD occlusion can occur due to various etiologies, but laser-vitreolysis is a non-invasive treatment option aimed at restoring tube patency and aqueous outflow.